Nierozróżniający wgląd w medytacji buddyzmu chan i jego wczesnobuddyjskie analogie - Kamil NOWAK (Argument, 2017)
Undifferentiating insight in the Chan Buddhist meditation and its early Buddhist analogies: In the paper a comparative analysis of Chan Buddhist meditation and the early Buddhist meditation has been conducted. In the first part the meditational instructions present in Zuochan yi and the corresponding texts of Chinese Buddhism have been demonstrated. Subsequently, based on those texts, the ideal type of Chan Buddhist meditation is created. The second part consists of the analysis of Aṭṭhaka‑vagga with the corresponding motifs from the other Pali Canon Suttas. The last part consists of a comparative analysis of the ideal type of Chan Buddhist meditation and meditation as shown in Aṭṭhaka‑vagga. The whole of the analysis aims at demonstrating the topos common for the early Buddhist tradition and Chan Buddhism.